Palliative radiation therapy in patients with metastasized pancreatic cancer - Description of a rare patient group - Habermehl, Daniel; Brecht, Ingo C.; Debus, Juergen; Combs, Stephanie E. (European Journal of Medical Research, 2014)
Background: Pancreatic cancer (PAC) patients experience a high rate of locoregional recurrences and distant metastasis finally leading to their demise even after curatively-intended multidisciplinary treatment approaches including surgery, chemotherapy and radiotherapy. However, clinical reports on bone and brain metastases in PAC patients are extremely rare and thus timing and dose description are not well defined. Our work therefore summarizes a mono-institutional experience on the use of radiotherapy (RT) for PAC patients with metastatic disease with the aim of identifying overall survival and treatment response in this rarely reported patient group. Method. Forty-four PAC patients with 66 metastatic lesions were treated with palliative radiotherapy (RT). Thirty-three patients (48 lesions), 7 patients (11 lesions) and 5 patients (7 lesions) with bone, liver and brain metastases analyzed respectively were analyzed; one patient had both bone and cerebral metastases and was treated for the lesions, thus including him in both subgroups. Indications for RT were pain, neurological impairment, risk of pathological fracture or imminent danger for development of any of these conditions in case of tumor progression. Median age was 64 years (range 38 to 78 years) and there were 27 male (61%) and 17 (39%) female patients. Analyses of overall survival (OS) and local control were performed. OS was calculated from the first day of RT. Results: Median overall survival (mOS) of all patients after start of RT was 4.2 months. Survival rates after 1, 3 and 6 months were 79.3%, 55.3% and 30.3% respectively. Patients presenting with bone metastasis had a mOS of 3.1 months and after 1, 3 and 6 months, survival rates were 75.3%, 46.5% and 19.9% respectively. Symptomatic response to therapy was recorded in 85% of all evaluated patients with bone metastasis. Patients undergoing radiosurgery because of liver metastasis were locally controlled in all but one patient after a median follow-up of 8.3 months. Conclusion: Overall survival of all patients with metastatic disease was considerably worse. A major goal for the future must be the selection of an appropriate RT treatment in terms of duration and technique for these PAC patients. © 2014 Habermehl et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Oligometastasis; Palliation; Palliative radiotherapy; Pancreatic cancer; Radiotherapy